2019
DOI: 10.1109/mwc.001.1900051
|View full text |Cite
|
Sign up to set email alerts
|

Physical Layer Security for Ultra-Reliable and Low-Latency Communications

Abstract: Ultra-reliable and low-latency communication (URLLC) is one category of service to be provided by next-generation wireless networks. Motivated by increasing security concerns in such networks, this article focuses on physical layer security (PLS) in the context of URLLC. The PLS technique mainly uses transmission designs based on the intrinsic randomness of the wireless medium to achieve secrecy. As such, PLS is of lower complexity and incurs less latency than traditional cryptography. In this article, we firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(26 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…Although it is possible to adopt the widely used cryptography algorithms, this may results into high-complexity signal processing and then not suitable for URLLCs, especially for IoT devices with low computing capacities. Recently, the adoption of physicallayer security (PLS) has been recognised a valid solution against eavesdropping attacks in URLLCs [75], [76]. Furthermore, the LoS-dominated UAV channel plays an important for physical layer keys generation aimed (PLKG) to generate the secret keys to protect the confidential information exchanged between transceivers [77].…”
Section: Urllc Securitymentioning
confidence: 99%
“…Although it is possible to adopt the widely used cryptography algorithms, this may results into high-complexity signal processing and then not suitable for URLLCs, especially for IoT devices with low computing capacities. Recently, the adoption of physicallayer security (PLS) has been recognised a valid solution against eavesdropping attacks in URLLCs [75], [76]. Furthermore, the LoS-dominated UAV channel plays an important for physical layer keys generation aimed (PLKG) to generate the secret keys to protect the confidential information exchanged between transceivers [77].…”
Section: Urllc Securitymentioning
confidence: 99%
“…The security concerns of eMBB and URLLC include internal communication, access control and malicious attack. Chen et al [71] have investigated security problems in URLLC applications. J.M.…”
Section: A Multi-sensory Xr Applicationsmentioning
confidence: 99%
“…Physical layer authentication (PLS) using L1 information is a good choice since it could remove the time-consuming functionalities of security protection for SRB0 and merely focus on inherent security advantages at L1 to bring lightweight overheads and desirable security performance [11]. Authors in [16] have analyzed the advantages of using physical layer information to protect URLLC. Previously, lots of research of PLS in [17], [18] have been done by employing channel state information (CSI) which is usually estimated using pilots.…”
Section: A Related Workmentioning
confidence: 99%
“…Authors in [32] also concluded that the technique of encoding SAPs to carry information in parallel with data transmission can improve the system reliability with less power and complexity, making it a very suitable candidate for 5G URLLC service. This technique was also studied in grant-free URLLC systems in [16]. Those schemes provide a road access to TRP using SAPs.…”
Section: A Related Workmentioning
confidence: 99%